2010
DOI: 10.1002/cssc.201000014
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen Production over Titania‐Based Photocatalysts

Abstract: Because of their relatively high efficiency, high photostability, abundance, low cost, and nontoxic qualities, titania-based photocatalysts are still the most extensively studied materials for the photocatalytic production of hydrogen from water. The effects of the chemical and physical properties of titania, including crystal phase, crystallinity, particle size, and surface area, on its photoactivity towards hydrogen generation have been identified by various investigations. The high overpotential for hydroge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
280
0
6

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 438 publications
(288 citation statements)
references
References 277 publications
2
280
0
6
Order By: Relevance
“…The trapping ability is largely determined by the work functions of the noble metals, which are greater than those of many semiconductors. Taking TiO 2 for an example, 6 a Schottky barrier can be formed at the metal/TiO 2 interface. Schottky barrier is a kind of junction which can facilitate charge separation ( Figure 1B).…”
Section: Cocatalysts For Water Reduction Half Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The trapping ability is largely determined by the work functions of the noble metals, which are greater than those of many semiconductors. Taking TiO 2 for an example, 6 a Schottky barrier can be formed at the metal/TiO 2 interface. Schottky barrier is a kind of junction which can facilitate charge separation ( Figure 1B).…”
Section: Cocatalysts For Water Reduction Half Reactionmentioning
confidence: 99%
“…Inspired by the above primary work, we further examined hydrogenase mimic [(μ-SPh-4-NH 2 ) 2 Fe 2 (CO) 6 ] (denoted as [Fe 2 S 2 ]) as the cocatalyst for H 2 evolution using semiconductor (ZnS) as the photoharvester and ascorbic acid (H 2 A) as the electron donor ( Figure 2B). 12 Remarkably, photocatalytic H 2 production with more than 2600 turnover numbers (based on [Fe 2 S 2 ]) and an initial TOF of 100 h À1 were achieved.…”
Section: Cocatalysts For Water Reduction Half Reactionmentioning
confidence: 99%
“…42 However, clean hydrogen production still remains a big challenge. 43,44 One possible way to produce clean hydrogen is via photocatalytic splitting of water on oxide surfaces using sunlight. 45 However, the low efficiency of such processes has hindered developments in this direction.…”
Section: Photocatalysis Of Methanol On Tio 2 (110)mentioning
confidence: 99%
“…Despite the difficulties, photocatalyzed splitting of water on TiO 2 surface has been extensively investigated, and many strategies have been proposed to increase the hydrogen production, e.g., loading TiO 2 with a noble metal or other semiconductor, doping, sensitizing and adding sacrificial species. 44 It has been reported that methanol is an effective sacrificial agent for hydrogen production. 46,47 Clearly, the photochemistry of methanol on TiO 2 plays a significant role in this process.…”
Section: Photocatalysis Of Methanol On Tio 2 (110)mentioning
confidence: 99%
“…TiO 2 (titania) is one of the most extensively studied semiconductor photocatalysts due to its potential to help overcome the worldwide energy shortage while also counteracting issues of climate change and environmental contamination [1][2][3]. Since the first report of its use for hydrogen generation via the photocatalytic decomposition of water by Fujishima and Honda [4], TiO 2 has attracted significant interest as a photocatalyst due to its favorable band edge positions, which are well-matched with the redox potentials of water, CO 2 , and a variety of organic compounds.…”
Section: Introductionmentioning
confidence: 99%